2013
DOI: 10.1007/s12272-013-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammatory cytokine gene polymorphisms on warfarin maintenance doses in Korean patients with mechanical cardiac valves

Abstract: Cytokines that are involved in inflammation are related to blood coagulation, which could indirectly affect warfarin dose requirements. This study aimed to examine the effects of inflammatory cytokine gene polymorphisms on warfarin dose requirements for Korean patients with mechanical heart valves. In total, 191 patients with mechanical heart valves who were on warfarin anticoagulation therapy and maintained INR levels of 2-3 for three consecutive occasions were retrospectively followed up. In addition to vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has previously been reported that warfarin dose requirements may be reduced in pro-inflammatory states. 15,21 In patients hospitalized with COVID-19, D-dimer, ferritin, and CRP are predictive of severity of illness and mortality. 22,23 Presence of a pro-inflammatory state represented by these markers may have contributed to the IP warfarin sensitivity and decreased dose requirements reported here.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that warfarin dose requirements may be reduced in pro-inflammatory states. 15,21 In patients hospitalized with COVID-19, D-dimer, ferritin, and CRP are predictive of severity of illness and mortality. 22,23 Presence of a pro-inflammatory state represented by these markers may have contributed to the IP warfarin sensitivity and decreased dose requirements reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin is considered to affect the inflammatory pathway in addition to its anticoagulant action (4,5). The dichotomic effect of warfarin means that at high concentrations, i.e., >200 mM of warfarin, high levels of interleukin-6 (IL-6) were observed in macrophage cells, therefore acting as pro-inflammatory, whereas at low warfarin concentrations, i.e., < 200 mM, there was inhibited tumor necrosis factor-α (TNF-α)-induced IL-6 release.…”
Section: Introductionmentioning
confidence: 99%